Graduate Professional Entry Courses in Accounting and Law : Final Report. - Jackson, Margaret; Cattlin, Joann; Lowe, Lillian; Scully, Glennda; Porter, Stacey; Mason, Rosalind; Cooper, Donna; Jackson, Sheryl (Australian Learning and Teaching Council (ALTC), 2012)
Final report from a project that examined the growing number of graduate entry courses being introduced by Australian universities which are designed to allow graduates to enter a new profession. To date, there has been limited work undertaken to understand the educational implications of these new courses, and to understand in particular the academic standards for postgraduate professional entry courses, as opposed to undergraduate courses also leading to professional entry. This project explored whether a masters level degree that meets the requirements for entry into a profession applies different academic standards from those applied in an undergraduate degree that also meets the same professional entry requirements. The project articulated what those different standards are or should be.